Protection Bissu right in the Bugis Arajang ritual - Khoidir, Muhammad; Mahfudz, Asep; Hermawati, Hermawati; Syaifullah, Syaifullah (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
The Bissu retain their "marginalised status" for various reasons, the most significant of which is their status as the custodians of the Arajang. This practice is in direct opposition to their religious beliefs. Secondly, they are subjected to discrimination due to their status as indigenous individuals who are members of the queer community. The Bissu's rights have been restricted in the performance of the Arajang ritual in 2022 and 2023, despite the efforts of the state authority, and more specifically, the provincial government, to address the issue. This article employs a qualitative approach with a case study design to comprehensively analyse the lack of performance of the Arajang ritual. In-depth interviews, documentation, and non-participant observation comprise the research methodology. The results suggest that the legal protections are insufficient to adequately safeguard the Bissu during the performance of rituals, as they are sociologically insufficient. Furthermore, the investigation revealed that leadership is a critical element in realising the rights of the Bissu people; however, normative legal guarantees have minimal influence on the capacity to intervene effectively.